P017 Echinocandin resistance mechanism in Candida tropicalis and Candida glabrata. (20th September 2022) - Sharma, Dipti; Paul, Raees A; Murlidharan, Jayashree; Sharma, Sadhna; Kaur, Harsimran; Ghosh, Anup K; Chakrabarti, Arunaloke; Rudramurthy, Shivaprakash M
Abstract: Poster session 1, September 21, 2022, 12:30 PM - 1:30 PM:   Objective: Candida tropicalis and Candida glabrata account for 41.6% and 7.08% of total Candida emia cases in India. Echinocandins are the first-line treatment option for these infections. Resistance to Echinocandins is rare with Candida sp. However, in recent years, has been noted across many centers. We determined the mechanism of echinocandin resistance in C. tropicalis and C. glabrata . Methods: C. tropicalis and C. glabrata isolated from Candida emia patients over a period of 3 years (August 2016-July 2019), identified by MALDI-TOF-MS were used in this study. Antifungal susceptibility testing was done following CLSI broth microdilution reference method (M 27A). FKS1 gene was sequenced using species-specific primers for the presence of any mutation. To determine any changes in the cell wall chitin and glucan contents, expression fold changes of chitin synthase (CHS1, CHS2, and CHS3), and glucan synthase genes upon caspofungin treatment were determined using real-time qPCR. These findings were correlated with cell wall chitin and glucan content determined by flowcytometry. Results: A total of 3558 Candida species were isolated from patients of all age groups at our hospital. C. tropicalis was the predominant agent (34%), while the prevalence of C. glabrata was 6%. A total of 17 (8.5%) C. glabrata and 3 (0.25%) C. tropicalis exhibited reduced susceptibility to echinocandins. All these isolates carried a wild-type FKS genes. In C. tropicalis, inducible expression of Chs1, Chs2 and Chs3 genes were comparable among susceptible and resistant isolates1.8 (0.4-2.8) vs. 2.5 (0.9-6.6), P  = .247); [0.7 (0.3-1.8) vs. 0.7 (0.2-1.6), P  = .793]; [1.3 (0.14-4.8) vs. 1.1(0.48-1.7), P  = .522], respectively. In concordance with gene expression, there was no significant difference in cell wall chitin contents among resistant and susceptible [14.37 (6.5-24.8) vs 16.28 (6.0-24.7), P  = .114] C. tropicalis isolates. In contrast in resistant isolates of C. glabrata, caspofungin treatment resulted in significantly higher induction of chitin synthase genes compared to susceptible isolates; Chs1 [2.34 (0.24-9.71) vs. 1.56 (0.55-4.5) ( P  = .007)], CHS2 [1.59 (0.33-8.0) vs. (2.3 (0.69-6.15), P  = .0006], and CHS3 gene [3.8 (0.13-12.73) vs. 1.9 (0.56-7.16), P  <.0001]. Flowcytometric data in terms of chitin content, correlated well with expression changes as staining index was significantly higher in resistant compared to susceptible isolates [320 (198-535) vs. 164 (5.34-254.10) P  = .0001]. Glucan synthase expression was comparable in susceptible and resistant isolates of C. tropicalis [3.47 (1.57-7.63) vs. 4.41 (0.41-17.51), ( P  = .518)]. However, glucan synthase gene expression was found significantly increased in resistant C. glabrata isolates compared to susceptible isolates; 3.10 (1.02-16.45) vs. 1.61 (0.13-7.67), P  <.001. Conclusion: We evaluated the role of cell wall components in echinocandin resistance in isolates with reduced susceptibility to echinocandins but lacking an FKS1 mutation. While chitin was induced at higher levels in C. glabrata, a similar finding was not observed in C. tropicalis . This warrants further studies to elucidate the role of fungal cell wall polymers in resistance.